1995
DOI: 10.1063/1.114187
|View full text |Cite
|
Sign up to set email alerts
|

Lasing operation up to 200 K in the wavelength range of 570–590 nm by GaInP/AlGaInP double-heterostructure laser diodes on GaAsP substrates

Abstract: New doubleheterostructure indiumtin oxide/InGaAsP/AlGaAs surface lightemitting diodes at 650nm range J. Appl. Phys. 66, 2181 (1989); 10.1063/1.344315 Continuous wave operation (77 K) of yellow (583.6 nm) emitting AlGaInP double heterostructure laser diodes Appl. Phys. Lett. 48, 557 (1986); 10.1063/1.96505 AlGaAs doubleheterostructure diode lasers fabricated on a monolithic GaAs/Si substrate Appl. Phys. Lett. 45, 309 (1984); 10.1063/1.95273 Roomtemperature cw operation of buriedstripe doubleheterostructure GaIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…1,2 More recent work has also been done, [3][4][5] but these research projects seem to have been abandoned in favor of the then newly demonstrated GaN-based materials as excellent short wavelength visible emitters. Thick graded layers ͑20-50 m͒ grown a͒ Electronic mail: mjmori@alum.mit.edu b͒ Electronic mail: sboles@alum.mit.edu by hydride vapor phase epitaxy ͑HVPE͒ were common, but total threading dislocation densities of the structure were still much higher than those of the native GaAs substrates ͑around 10 6 cm −2 ͒.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…1,2 More recent work has also been done, [3][4][5] but these research projects seem to have been abandoned in favor of the then newly demonstrated GaN-based materials as excellent short wavelength visible emitters. Thick graded layers ͑20-50 m͒ grown a͒ Electronic mail: mjmori@alum.mit.edu b͒ Electronic mail: sboles@alum.mit.edu by hydride vapor phase epitaxy ͑HVPE͒ were common, but total threading dislocation densities of the structure were still much higher than those of the native GaAs substrates ͑around 10 6 cm −2 ͒.…”
Section: Motivation and Backgroundmentioning
confidence: 99%